(untitled) (Fiep Bulletin - online, 2014)
The incidence of the breast cancer has been increasing everywhere in the world, making this disease one of the largest public health problems. In most of the cases, the surgical treatment is indicated. There are several complications post-mastectomy, among them the pain, the postural deviations and the joints blockades. GPR is a method of postural re-education that aims to treat pathologies that require physical therapy, such as joint, traumatic and breathing problems. The objective of this work was to verify the effectiveness of Global Postural Re-education® in a patient submitted to modified radical mastectomy. A woman participated in this study submitted to modified radical mastectomy of the left breast. The patient was photographed frontally, in profile and back, in the first and in the last appointment. In the first appointment, the patient presented for EVA 10 in pain, totally dissatisfied with the limitations, and great blockade in the joint of the shoulder and in the thoracic box in the left hemi body, with 90º of flexion and 40º of abduction. In the last appointment, we found EVA 3 in pain, however just when carrying out the movements beyond AOM accomplished already, and blockade only in the area of the shoulder, but already showing herself more satisfied, with 160º of flexion and 65º of abduction. Comparing the two moments of the images, we have a better AOM, with reduction of the joint blockade, alignment of the shoulders, and a very significant improvement of the thoracic expansion. The treatment reduced the complaint of pain, increased AOM of the shoulder significantly without great compensations and improved the posture when compared to the posture previous to the intervention of GPR.